Incidence And Clinical Factors Of Retention Of Fetal Membranes In Dairy Bovines Of Anand District - Thavani, K.L.; Patel, J.A.; Dhami, A.J.; Parmar , S.M. (Indian Journal of Veterinary Sciences and Biotechnology, 2011)
The overall incidence of RFM in dairy bovines of Amul milk shed area of Anand district during the year 2010-11 was found to be 46.37 per cent of the total reproductive disorders (27480/59267) and as 4.81 per cent of the total clinical cases (27480/571080) attended. The highest incidence was observed during monsoon (45.52 %) followed by winter (32.66 %) and the least in summer (21.82 %). Further, an epidemiological investigation was carried out on 50 Surti buffaloes with RFM managed at the farmers’ door revealed that the sex of calf and suckling/weaning had no effect on the incidence of RFM. The maximum number of RFM cases were observed in buffaloes of third parity (32 %) followed by second (20 %) and fourth (16 %) parity. With the increase in the quantity of concentrate feeding, the incidence of RFM decreased. The effect of previous parturient abnormalities showed less effect on RFM in buffaloes. However, as the birth weight of calf increased, the incidence of RFM increased.